Effect of a Dietary Probiotic Supplement on the Haematological Status of Experimental Wistar Rats Infected with Trypanosoma brucei brucei - (:unkn) unknown (My University, 2024)
Animal African Trypanosomiasis (AAT) is a debilitating protozoan disease of domestic animals caused by Trypanosoma spp. which remains a major setback to animal health and the livestock industry in sub-Saharan Africa. The effect of treatment with probiotic on the haematological changes in Wistar rat infected with Trypanosoma brucei brucei was investigated. The probiotic strain used was Lactobacillus acidophilus. Twenty-four male wistar rats randomly assigned to six groups were used in the experiment. The different groups were treated with the probiotics such that Groups A and B were the negative and positive controls, respectively. On the other hand, Groups C to F were given 2 × 108 CFU, 5 × 108 CFU, and 8 × 108 CFU of the probiotic daily, respectively, and monitored for haematological variations from day 1 post supplementation (PS) to termination on the 18th day. The study found significant difference in lymphocyte concentration, platelet concentration, white blood cell (WBC), red blood cell (RBC), haemoglobin, and packed cell volume (PCV) among different treatment groups. Group C had the highest lymphocyte concentration (74.00±1.00), while group B had the highest platelet concentration (171.00 ±1.00). The results of this study suggested that oral administration of the probiotics (Lactobacillus acidophilus) supplement ameliorated the negative effect of Trypanosoma brucei brucei infection on the haematology of wistar rat. Oral administration of the probiotics (Lactobacillus acidophilus) supplement could therefore be incorporated in the management protocol of Animal African Trypanosomiasis (AAT).
Keywords: African Research